High-Throughput Expression of C. elegans Proteins - Luan, Chi-Hao; Qiu, Shihong; Finley, James B.; Carson, Mike; Gray, Rita J.; Huang, Wenying; Johnson, David; Tsao, Jun; Reboul, Jérôme; Vaglio, Philippe; Hill, David E.; Vidal, Marc; et al.

(untitled) (Genome Research, 2004)
Proteome-scale studies of protein three-dimensional structures should provide valuable information for both investigating basic biology and developing therapeutics. Critical for these endeavors is the expression of recombinant proteins. We selected Caenorhabditis elegans as our model organism in a structural proteomics initiative because of the high quality of its genome sequence and the availability of its ORFeome, protein-encoding open reading frames (ORFs), in a flexible recombinational cloning format. We developed a robotic pipeline for recombinant protein expression, applying the Gateway cloning/expression technology and utilizing a stepwise automation strategy on an integrated robotic platform. Using the pipeline, we have carried out heterologous protein expression experiments on 10,167 ORFs of C. elegans. With one expression vector and one Escherichia coli strain, protein expression was observed for 4854 ORFs, and 1536 were soluble. Bioinformatics analysis of the data indicates that protein hydrophobicity is a key determining factor for an ORF to yield a soluble expression product. This protein expression effort has investigated the largest number of genes in any organism to date. The pipeline described here is applicable to high-throughput expression of recombinant proteins for other species, both prokaryotic and eukaryotic, provided that ORFeome resources become available.